The Pressure, The Opportunity and The Understanding of Tri Pantangan Tamansiswa (Tamansiswa’s Three Constrictions) on Student Academic Cheating - Wardani, Dewi Kusuma; Lestari, Diana (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
Higher education has a crucial role in preventing various forms of cheating behaviour that, unfortunately, often occur among students. Academic cheating is a reasonably exciting problem that is currently getting attention in the world of higher education. Generally, students focus more on the results than on the process. As a result, cheating practices in the academic environment are increasingly being carried out to obtain the desired results, which are then known as academic fraud. Therefore, this study aimed to analyse the differences in influence between three experimental groups (independent) and one comparison group (dependent), namely the impact of influence on student academic fraud. This study uses a descriptive quantitative design adopted. The data collection method uses a questionnaire. The data collection instruments used in the questionnaire included pressure, opportunity, the teachings of the three taboos, and academic cheating. Multiple linear regression analysis was used to evaluate the data. The results of the research are that pressure and the Three Abstinences have a negative effect on student academic cheating, while opportunity and pressure have a positive effect on student academic cheating. The research implication is that pressure, opportunity, and understanding the teachings of the three taboos influence student academic cheating so that educational institutions need to increase the cultivation of moral values, such as understanding the teachings of the Tri Pantangan (three restriction), and also reduce opportunities for pressure, to be able to reduce student academic cheating